ASSESSMENT OF ORGANIC PHOSPHORUS DISTRIBUTION IN THE SEDIMENT AND WATERS OF LANGAT RIVER - Micheal Charles Rajaram; Muskhazli Mustafa; Nor Azwady Abd Aziz; Noor Haza Fazlin Hashim; Bashirah Mohd Fazli; Bilyaminu Garba Jega (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Langat River water and sediment quality deteriorate toward downstream.- Dissolved organic phosphorus increases near agricultural areas.- Sediment phosphate retention dominated by non-labile organic phosphorus.- Downstream pollution linked to sediment sorption and nearby agriculture.ABSTRACTThe Langat River traverses rapidly developing urban areas in Malaysia and is significantly affected by anthropogenic activities. The introduction of excessive phosphorus into rivers poses a significant ecological issue. Water and sediments were sampled from nine stations at Langat River to evaluate the current and potential impacts of organic phosphorus. The water quality parameters indicate a progressive decline downstream, attributed to allochthonous sources from tributaries and land use practices, particularly agriculture. Inorganic substances are the principal cause of pollution in the river while degradation of organic pollution biologically is reduced. Dissolved organic phosphorus (DOP) plays a significant role at stations that are either relatively unpolluted or adjacent to agricultural areas, serving as a potential source of bioavailable phosphorus. The total organic phosphorus in the sediment increased downstream, predominantly comprising non-labile fractions (67–78%). The labile fractions exhibit strong correlations with dissolved oxygen (DO) (r = -0.797), dissolved organic phosphorus (DOP) (r = 0.931), and conductivity (r = 0.837), suggesting internal loading to the water column. Increased non-labile fractions indicate the sediment's capacity to retain organic phosphorus. The downstream stations exhibit elevated risk owing to high sorption capacity and proximity to agricultural sources of organic phosphorus.